Evaluation of annealing and double ion beam irradiation by a laser-induced and laser-detected surface acoustic wave diagnostic system. (October 2016) - Kitazawa, Sin-iti; Wakai, Eiichi; Aoto, Kazumi
Abstract: The effects of annealing and double ion irradiation on nuclear structural materials were investigated using a novel, non-destructive, non-contact diagnostic method. A laser-induced and laser-detected surface acoustic wave (SAW) was adopted as a diagnostic system. The SAWs propagation velocity and the SAWs vibration velocity along the normal direction of the surface were measured to investigate mechanical properties of the substrates. Change of the shear modulus was detected in the annealed substrates. Non-linear effect on amplitude of the excited SAW was observed on the double ion irradiated materials. The potential of the SAW diagnostic system for assessing nuclear structural materials was demonstrated. Highlights: We modified the surface of specimens by heat treatment and double ion beam irradiation. The diagnostic was performed by observation of SAWs. A non-linear nature of SAWs indicates changes in the mechanical properties. The potential of the SAWs diagnostic system was demonstrated.